(untitled) (Forum Penelitian Agro Ekonomi, 2016)
English Utilization of dry land for farming activities in Indonesia is presently less optimal compared with its availability. In order to overcome the "big puzzle" of multidimensional crisis which is induced by monetary crisis in mid of 1997, more attention of the Indonesian government on dry land farming represents a key factor. The implementation of appropriate strategy in developing agribusiness in the dry land region is very important to overcome both the short term economic problem induced by the crisis, and the long term national development problem through its external benefit in reducing environment problem and natural resources degradation. In this relation, efforts required are : (1) Infrastructures development particularly in outer island of Java where most of dry land were located, (2) Arrangement of dry land use on the basis of river basin area in such away to ensure good performance of water circulation system. In this relation, development of appropriate commodities to the land use planned and land distribution forms an important strategy, (3) Policy makers especially in "Ekuin Circle" should put more attention to the development of local resources economic base. To ensure sustainable economic development the government should allocate more investment in the dry land area. ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â Indonesian Pemanfaatan lahan kering di Indonesia hingga dewasa iniÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â masih jauh dari optimal. Untuk menjawab "teka-teki besar" krisis multi dimensi, yang berawal dari krisis ekonomi 1997, dan memperkecil peluang terjadinya pengulangan krisis di kemudian hari, masyarakat Indonesia perlu melihat lahan kering sebagai salah satu kunci pembukanya. Pemberdayaan lahan keringÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â untuk pengembangan agribisnis bukan saja akan dapat membantu mengatasi stagnasi dan krisi ekonomi dalam jangka pendek, tetapiÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â dalam jangka panjang akan memberikan manfaat eksternal yang relatif besar di bidang penyehatan ekosistem, pemeliharaan sumberdaya alam dan pengembangan perspektif kegiatan ekonomi berwawasan kebangsaan secara lebih luas. Dalam kaitan itu tersebut beberapa upaya yang diperlukan dalam rangka pemberdayaan lahan kering yaitu: (1) Pembangunan infrastruktur ekonomi di luar Jawa di mana lahan kering terhampar luas, (2) Penataan pola pemanfaatan lahan kering terhampar relatif luas, (2) penataan pola pemanfaatan lahan kering dengan pendekatan wilayah DAS sedemikian rupa sehingga sistem lingkungan dan sirkulasi air berlangsung secara baik. Dalam kaitan ini, pengembangan komoditas pertanian yang sesuai dengan tat guna lahan dan distribusi penguasaan lahan merupakan langkah penting, (3) Perancang kebijakan pembangunan di kalangan ekuin harus lebih memperhatikan pembangunan sektor ekonomi yang berlandaskan pada kekuatan sendiri. Untuk menjamin pembangunan ekonomi secara berkelanjutan maka pemerintah perlu lebih mengarahkan investasinya ke wilayah lahan kering.